Ethical Dilemmas in Developing a Vaccine to Prevent COVID-19: The Perspective of Jewish Ethics - Rashi, Tsuriel (Theology and science, 2022)
In March 2020, the WHO declared COVID-19 a pandemic, and there was a worldwide race to find an effective drug and/or vaccine. I present the Jewish ethical approach to two quandaries facing researchers: What is the acceptable degree of risk to the sick and to the healthy volunteers who participate in tests of an experimental vaccine? Is it permissible for a healthy person to volunteer for clinical trials? My conclusions are that a higher degree of risk is permissible in life-threatening situations, and it is right and proper that healthy people may volunteer even it involves exposing themselves to danger.